[3+2]‐Cycloadditions of N‐Cyano Sulfoximines with 1, 3‐Dipoles. Issue 18 (20th April 2020) - Krauskopf, Felix; Truong, Khai‐Nghi; Rissanen, Kari; Bolm, Carsten
Abstract : Involving the cyano group of N ‐cyano sulfoximines in [3+2]‐cycloaddition reactions with 1, 3‐dipoles provides practical routes for the construction of 5‐membered heterocycles bearing sulfoximinoyl moieties. An ytterbium‐catalyzed cycloaddition utilizing hydrazonoyl chlorides was developed, as well as a reaction involving imidoyl chlorides proceeding without the aid of a catalyst. Following these protocols, a range of sulfoximines with N ‐1, 2, 4‐triazolyl and N ‐1, 2, 4‐oxadiazolyl substituents was prepared. Abstract : In the present study reports 1, 3‐dipolar cycloaddition reactions starting from easily accessible N ‐cyano sulfoximines. In a straightforward manner, sulfoximines with N ‐1, 2, 4‐triazolyl and N ‐1, 2, 4‐oxadiazolyl substituents are prepared in good yields, While the former reactions require the presence of Yb(OTf)3 in catalytic amounts, the latter proceed metal‐free.